Effect of annealing treatment on sputtered copper oxide thin film. (2018) - Sangwaranatee, N.; Horprathum, M.; Chananonnawathorn, C.; Hendro,
Abstract: Copper oxide thin films were prepared on silicon wafer and glass slide substrate by dc reactive magnetron sputtering using a copper target without substrate heating. As-deposited CuO thin films were then annealed at various the temperatures in air ambient. The effects of annealing treatment on the physical morphology, optical property of the prepared samples were studied by glancing incident X-ray diffraction (GIXRD), field-emission scanning electron microscopy (FE-SEM), UV-Vis-NIR spectrophotometer. The results shown that the crystallinity of the CuO thin films was significantly improved as an annealing temperature increased. Additionally, the sheet resistance measurements were characterized on as-deposited and annealed samples in order to discuss the electrical properties.